First case of methemoglobinemia caused by a ClO2‐based household product. Issue 6 (3rd September 2015) - Hagiwara, Yusuke; Inoue, Nobuaki
Abstract: When new household products are developed and distributed, new injuries often occur in children. We report the first known case of methemoglobinemia caused by a chlorine dioxide (ClO2 )‐based household product. A 1‐year‐old boy presented to the emergency department with vomiting and poor complexion after accidentally ingesting a ClO2 ‐based household product. The patient had profound hypoxia that did not respond to oxygen therapy and required endotracheal intubation to maintain a normal oxygen level. Although oxygen saturation (SpO2 ) fluctuated at approximately 95% after intubation, arterial oxygen pressure (PaO2 ) was high on arterial blood gas analysis. We suspected methemoglobinemia based on the gap between SpO2 and PaO2, and subsequently detected increased methemoglobin at 8.0%. The patient was admitted to the pediatric intensive care unit for further management. After supportive treatment, he was discharged without any complications. He had no cognitive or motor dysfunction on follow up 3 months later.